GAZ NÍZAMLARÍN GAZLÍ TERMOMETR JÁRDEMINDE ÚYRENIW - Jalelov, M.A.; Otarbaev, A.E.; Jaksimuratov, I.J. (SCIENCE and SOCIETY, 2021)
This article the discusses the methods for studying ideal gas laws. Emphasizing the importance of studying the laws of Charles and Boyle-Marietta using a gas thermometer and the expected results.